QCD analysis of W- and Z-boson production at Tevatron - Camarda, Stefano; Belov, P.; Cooper-Sarkar, A. M.; Diaconu, C.; Glazov, A.; Guffanti, A.; Jung, A.; Kolesnikov, V.; Lohwasser, K.; Myronenko, V.; Olness, F.; Pirumov, H.; et al. (The European physical journal. C, Particles and fields, 2015)
Recent measurements of the W-boson charge asymmetry and of the Z-boson production cross sections, performed at the Tevatron collider in Run II by the D0 and CDF collaborations, are studied using the HERAFitter framework to assess their impact on the proton parton distribution functions (PDFs). The Tevatron measurements, together with deep-inelastic scattering data from HERA, are included in a QCD analysis performed at next-to-leading order, and compared to the predictions obtained using other PDF sets from different groups. Good agreement between measurements and theoretical predictions is observed. The Tevatron data provide significant constraints on the d-valence quark distribution.
Gesehen am 03.11.2020